2021
DOI: 10.3390/vetsci8020013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Delivery Format on Student Outcomes and Perceptions of a Veterinary Medicine Course: Synchronous Versus Asynchronous Learning

Abstract: The COVID-19 pandemic prompted instruction at many veterinary schools to switch to an emergency remote teaching format to prevent viral transmission associated with in-person synchronous lectures. This study surveyed student perspectives and academic performance in a pre-planned online second-year veterinary toxicology course given at North Carolina State University in Spring 2020. This course relied on asynchronous narrated presentations for content delivery. This method of delivery predated the pandemic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Additionally, they are convenient in case of Internet‐related issues, such as availability, connectivity, and speed (Rashid et al, 2020). Frequent access to asynchronous learning materials enhances veterinary students' performance (Schoenfeld‐Tacher & Dorman, 2021). The current study showed that the veterinary school followed the asynchronous mode of teaching and the learning materials provided to students through the university platform were either PowerPoint slides with recorded voice or pdf format.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they are convenient in case of Internet‐related issues, such as availability, connectivity, and speed (Rashid et al, 2020). Frequent access to asynchronous learning materials enhances veterinary students' performance (Schoenfeld‐Tacher & Dorman, 2021). The current study showed that the veterinary school followed the asynchronous mode of teaching and the learning materials provided to students through the university platform were either PowerPoint slides with recorded voice or pdf format.…”
Section: Discussionmentioning
confidence: 99%
“…The study designs include cross-sectional, case–control, mixed, and qualitative study designs. Most studies are at Kirkpatrick level 1, while three of them are at level 2 [ 29 31 ] and two are at level 3 [ 26 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…54% agreed that OL engagement, increase motivation, and build their interest. However, only 37.6% supported OL 1 Schoenfeld-Tacher & Dorman (2021) [ 31 ] OL; UG veterinary students from North Carolina State University Online questionnaire Traditional learning ( N = 103) Cross-sectional study Students (52.6%) agreed that the OL performs almost the same with f2f, 15.8% thought OL was better. Benefits, include increased motivation and flexibility of time and place.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The students could attend the recitations live on Zoom, but some of them chose only to follow them asynchronously, confirming the post-pandemic literature (cfr. [40]) that stated that the added liberty in choosing when to follow classes could outweigh the advantage of being able to interact with the teacher; 17 students mentioned the availability of lecture captures-which, at the University of Milan, were still a novelty in March 2020-as a plus, and one student stated that recordings made it possible for him to reconcile his summer job with the course. It should be mentioned that five students were working during the summer, and two gave up a summer job in order to spend enough time on the course.…”
Section: Working At a Distancementioning
confidence: 99%